Social Interaction, Socio-Economic Status, and Basic Economic Knowledge of Students' Economic Behavior - Siti Nurul Qomariyah; Harti; Hariyati (Faculty of Economics, State University of Jakarta., 2019)
This study aims to determine the effect of social interaction, socioeconomic status and basic economic knowledge on the economic behavior of MAN students in the Pati Regency. This research uses a quantitative research approach. This study uses primary data obtained from distributing questionnaires to students. The population in this study amounted to 266 students. A sample of 160 students with a proportional random sampling technique. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis, there is an influence of social interaction, socioeconomic status and basic economic knowledge on the economic behavior of MAN students in Pati Regency. This is indicated by the results of the F Test which obtained a significance value of 0.00 < 0.05.